Kecerdasan Majemuk Pada Anak Muslim: Perspektif Al-Qur’an Dan Al-Hadits - Nurhidayati, Titin; Fitri, Luluk (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Multiple intelligences or Multiple Intelligences is a theory coined by Howard Gardner in 1983 at Harvard University Project Zero. This theory presents nine human intelligences: linguistic, logical-mathematical, spatial, bodily-kinesthetic, musical, interpersonal, intrapersonal, naturalist, and existential. The emergence of the theory of multiple intelligences was born from Howard Gardner's criticism of the theory Intellectual Quotient (IQ). According to Gardner intelligence is more than just (IQ)Intellectual Quotient, children should be judged on what they can do, not what they cannot do. This theory shows that every child has their own uniqueness which deserves recognition and appreciation in life, especially in education. Development in multiple intelligences can be carried out using educational methods including Islamic education methods. This is done to build a comprehensive Islamic education process that can maximize multiple intelligences in children.